Historical blocking: CN 2023-11-15 to 2023-11-17 (China) - Voidly (2023)
CRITICAL severity censorship detected in China. Confidence: 97%. Data sourced from ooni-historical-backfill.
Censorship Incident ID: CN-2023-0539
Keywords: censorship; CN; censorship; critical